Manajemen Dana Bank Syariah Dalam Perspektif Islam - Hadi, Nur; Wijaya, Irwanda Ardhi (LPPM Institut Pendidikan Nusantara Global, 2024)
The fundamental precepts of Islamic jurisprudence, which proscribe usury and ambiguity, serve as the cornerstone for the operational framework governing fund management within Islamic banking institutions. Various financial products and services pertaining to fund management, including Islamic financing and trust investment, are structured to afford clientele the opportunity to administer their assets in alignment with Shariah tenets. It is imperative to recognize that fund management within Islamic banks transcends mere technical proficiency, encompassing a profound ethical dimension inherent in the delivery of financial services. The primary objective of this investigation is to elucidate the multifaceted role of Islamic banks as not solely profit-centric entities, but as catalyzing agents of societal transformation, advocating principles of equitable distribution and enduring economic viability. As Islamic banks assume an increasingly prominent position within the global financial landscape, empirical findings underscore their capacity to effectuate positive socio-economic change through adept investment strategies and judicious utilization of technological resources. This empirical inquiry underscores the potential of Islamic banks to foster equitable and sustainable economic development consonant with the precepts delineated in the Quranic scripture, Hadith traditions, and scholarly consensus.